Cut-off point for diagnosing thoraco-lumbo-pelvic rotation range hypomobility through the leg lateral reach test in chronic low back pain: a cross-sectional study - Pontes-Silva, André; Santos-de-Araújo, Aldair Darlan; Schamas-Esposel, Mariana; Araujo, Aliny da Silva de; Gaban, Giovanna Laura Neves Antonio; Dibai Filho, Almir Vieira (São Paulo Medical Journal, 2026)
BACKGROUND: Studies have proposed using the leg lateral reach test (LLRT). However, they did not establish a cut-off point for testing. OBJECTIVE: To establish a cut-off point for the thoraco-lumbo-pelvic rotation range using the LLRT in patients with chronic low back pain. DESIGN AND SETTING: Cross-sectional study conducted in Buriticupu, Maranhão, Brazil. METHODS: In the chronic low back pain group (LBPG, n = 35), we included patients aged 18 to 59 years, of both sexes, with scores ≤ 4 on the Baecke Habitual Physical Activity Questionnaire, body mass indeces ≤ 26 kg/m2, disability levels ≥ 3 on the Roland-Morris Disability Questionnaire, and pain levels ≥ 3 on the Numeric Pain Rating Scale. In the healthy control group (HCG, n = 35), the patients had the same characteristics (except for pain and disability). We used receiver operating characteristic curves to check the rate of true versus false positives in different LLRT ranges of motion and found the best LLRT cut-off point using the following mathematical model: (1 – sensitivity)2 + (1 – specificity)2. RESULTS: The sample was mainly composed of females (HCG = 65.71%; LBPG = 82.85%, P = 0.101), and 68.42% of the characteristics (13 of 19 comparisons between groups) showed a significant difference (P ≤ 0.05), with an effect size ranging from moderate to large (Cohen’s d ≥ 0.5). The cut-off value for ideal sensitivity and specificity was ≤ 82.85 cm. CONCLUSION: Patients with chronic low back pain and an LLRT range ≤ 82.85 cm have hypomobility regarding thoraco-lumbo-pelvic rotation range.